North-south environmentalisms: Friends of the Earth International (FOEI) - Doherty, B.; Doyle, Timothy (Palgrave MacMillan, 2012)
In times of global crisis, or in the wake of disaster, non-governmental public actors play key roles in assisting states and providing relief. They also have crucial roles in advocating for changes: in societies, in laws and even to regimes. This unique collection of comparative studies on the politics of non-governmental public action at the global level explores themes such as child rights, access to medicine, global security and environmentalism. The contributors investigate how non-governmental public actors engage in global policy processes and how this in turn affects their activities and their relations with each other. They discuss the tensions of organising globally, revolving around different political agendas in the 'North' and 'South', different ideological starting-points and differential access to resources and opportunities. While non-governmental public action at the global level can make a difference to issues and policies both globally and domestically, acting globally also brings with it tensions, contradictions and complex power relations that shape how non-governmental public action unfolds.